Porous Al/Al2O3 two-phase nanonetwork to improve electrochemical properties of porous C/SiO2 as anode for Li-ion batteries - Cui, Jinlong (2021)
Although C/SiOx (0 < x ≤ 2) composites are considered promising candidates as next-generation anode materials, their lower initial Coulombic efficiency and poor cycling stability seriously limit their commercial applications. In this study, a smooth porous Al2O3 protective layer containing pure Al is introduced onto the surfaces of porous C/SiO2 composites and the inside walls of their pores to prepare Al-doped porous C/SiO2 composites via a high-temperature solid-state method. This porous Al/Al2O3 two-phase network, ∼4 nm in thickness, is effective in obstructing the formation of a thick solid-electrolyte interface film and the dissolution of electrode materials by HF during cycling, thus significantly heightening the initial Coulombic efficiency and cycling stability of the porous C/SiO2 electrode. The pure Al nanoparticles in this Al/Al2O3 nanonetwork also enhance the electronic conductivity of the Al2O3 protective layer. When used as anode materials for Li-ion batteries, the resulting composites deliver a reversible specific capacity of 1385 mAh/g at a current density of 0.1 A/g, with an improved initial Coulombic efficiency of 80.47%, compared to that of porous C/SiO2 (41.90%). Even at 1.6 A/g, the specific capacity is also maintained at 583.1 mAh/g with a capacity loss of only 4.08% after 1200 cycles.